Open-Label Placebo Interventions With Drinking Water and Their Influence on Perceived Physical and Mental Well-Being - Rathschlag, Marco; Klatt, Stefanie (Frontiers in Psychology, 2021)
In recent years, the postulation that deception is necessary for placebos to have an effect on pain relief or increased well-being has come into question. Latest studies have shown that an openly administered mock drug works just as well as a deceptively administered placebo on certain complaints. This open-label placebo effect has primarily been used in the area of pain treatment so far. This study is the first to examine the effect of such placebos on healthy individuals with the use of drinking water. In two experiments, participants were required to use certain specified water bottles for their daily drinking water consumption. At the beginning of Experiment 1, all participants (N = 68) received one bottle of water, which they were asked to refill themselves each day during a 2-week intervention period. In Experiment 2, participants (N = 75) received a new sealed water bottle every day. In both experiments, participants were randomly assigned to one of four groups: no treatment (control group CG), open-label placebo without rationale (OPR–), open-label placebo with rationale (OPR+), and open-label placebo with additional rationale in a suggested relaxed state (group OPR++). We conducted baseline and post-treatment measurements of the subjective perceived physical and mental well-being of the participants. In Experiment 1, only the OPR++ group reported enhanced vitality at the post-treatment level compared to the other groups. In Experiment 2, post-treatment measurements showed improvements for the OPR++ group in the Physical Performance Capability, Mental Performance Capability, Emotional Balance, Overall Recovery, Negative Emotional State, and Overall Stress categories compared to the other groups. Our results support the idea that placebos with an additional rationale in a suggestive relaxed state are more effective than with just a rationale in a normal state. Furthermore, our study shows the tendency that OLP++ in the form of water with health claims may be more effective when the water is given in several sealed bottles separately than in one sealed but refillable bottle.